Criticizing Female Genital Mutilation Practice from Feminist Standpoint Theory: A View from Communication Science Perspective - Hendar Putranto (Jurnal Humaniora, 2022)
This conceptual review examines Female Genital Mutilation (FGM) practice in Indonesia viewed from Feminist Standpoint Theory (FST). The current study uses a literature review to build an argumentative contribution from communication science perspective. FGM is a global phenomenon locally and culturally practiced in more than 29 countries, including Indonesia. Despite many state regulations and international treaties forbidding the practice because of its harmful consequences, FGM practice is persistently maintained by religion, culture, tradition, and other factors. The author proposes FST as a theoretical base to criticize FGM because it does not represent the lived experience of women, marginalizes women further to the brink of ideal democratic participation, and does not contribute towards the positive construction of female selfhood. The author will elaborate on these three objections using the communication science perspective within the Indonesian cultural context. The author proposes more action-oriented theorizing to overcome FST's practical deficiency by providing insights from critical intercultural communication. Women's collective agency based on situated knowledge will empower their communicative skills as enablers of transformation to eradicate FGM.